2022
DOI: 10.1038/s41598-022-19640-4
|View full text |Cite
|
Sign up to set email alerts
|

Perceptual decision-making in autism as assessed by “spot the difference” visual cognition tasks

Abstract: Discriminating between similar figures proves to be a remarkably demanding task due to the limited capacity of our visual cognitive processes. Here we examine how perceptual inference and decision-making are modulated by differences arising from neurodiversity. A large sample of autistic (n = 140) and typical (n = 147) participants completed two forced choice similarity judgement tasks online. Each task consisted of “match” (identical figures) and “mismatch” (subtle differences between figures) conditions. Sig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 69 publications
0
1
0
Order By: Relevance
“…However, more recent work has suggested that autistic individuals may be slower to process global wholes (Koldewyn et al, 2013), or may merely be less inclined to use global-to-local processing strategies during visuospatial tasks (Van der Hallen et al, 2015). In line with this, autistic individuals have been found to differ in their response strategies during two alternative forced-choice figure dis-embedding tasks (Jassim et al, 2022). To minimise the role of explicit cognitive strategies, we propose that the use of indirect measurements may better capture the automatic and implicit aspects of perception in autism.…”
Section: Introductionmentioning
confidence: 91%
“…However, more recent work has suggested that autistic individuals may be slower to process global wholes (Koldewyn et al, 2013), or may merely be less inclined to use global-to-local processing strategies during visuospatial tasks (Van der Hallen et al, 2015). In line with this, autistic individuals have been found to differ in their response strategies during two alternative forced-choice figure dis-embedding tasks (Jassim et al, 2022). To minimise the role of explicit cognitive strategies, we propose that the use of indirect measurements may better capture the automatic and implicit aspects of perception in autism.…”
Section: Introductionmentioning
confidence: 91%